Respuestas

2012-09-29T01:14:49+02:00

x² + y² + ax + by + c = 0


16 + 25 + 4a + 5b + c = 0 ⇒ 4a + 5b + c = -41
9 + 4 + 3a - 2b + c = 0 ⇒ 3a - 2b + c = -13
1 + 16 + a - 4b + c = 0 ⇒ a - 4b + c = -17

a = -17 + 4b - c
3(-17 + 4b - c) - 2b + c = -13 ⇒ 10b - 2c = 38 ⇒ (por 3) ⇒ 30b - 6c = 114
4(-17 + 4b - c) + 5b + c = -41 ⇒ 21b - 3c = -27 ⇒ (por -2) ⇒ -42b + 6c = -54

30b - 6c = 114
-42b + 6c = -54
-12b = 60
b = 60/(-12)
b = -5

10(-5) - 2c = 38
-50 - 2c = 38
-2c = 38 + 50
-2c = 88
c = 88/(-2)
c = -44

a = -17 + 4(-5) - (-44)
a = -17 - 20 + 44
a = 7

x² + y² + 7x - 5y - 44 = 0

(x + 7/2)² + (y - 5/2)² - 44 = 49/4 + 25/4
(x + 7/2)² + (y - 5/2)² = 37/2 + 44
(x + 7/2)² + (y - 5/2)² = 125/2

también podrías buscar la intersección de la mediatrices
(x + y + 1 = 0, x + 7y - 14 = 0)